2022
DOI: 10.3390/ani12050539
|View full text |Cite
|
Sign up to set email alerts
|

Differential Expression of MSTN Isoforms in Muscle between Broiler and Layer Chickens

Abstract: Myostatin (Mstn)-A, the main isoform among Mstn splicing variants, functions as a negative regulator, whereas Mstn-B functions as a positive regulator in muscle development. Because broiler chickens are a fast-growing breed raised for meat production and layer chickens are a slow-growing breed raised for egg production, differences in the expression of Mstn isoforms between the two distinct breeds were analyzed in this study. There was no difference in the expression levels of total Mstn (Mstn-A and -B forms) … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
14
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
8

Relationship

3
5

Authors

Journals

citations
Cited by 9 publications
(15 citation statements)
references
References 20 publications
1
14
0
Order By: Relevance
“…Mstn is a negative regulator in muscle growth and development, and is expressed almost exclusively in mature skeletal muscle . The inhibitory role of Mstn in muscle development was further confirmed in numerous species of domesticated animals with double muscled phenotypes, including sheep, chicken, mice, cattle, and pigs Kijas et al, 2007;Stinckens et al, 2008;Kim et al, 2022). Similar to our previous study (Lee et al, 2020), Mstn knock-out quail exhibited significantly heavier BW and greater breast muscle mass than WT quail, suggesting conserved function of Mstn in regulation of muscle growth between mammals and avian species.…”
Section: Discussionsupporting
confidence: 85%
See 1 more Smart Citation
“…Mstn is a negative regulator in muscle growth and development, and is expressed almost exclusively in mature skeletal muscle . The inhibitory role of Mstn in muscle development was further confirmed in numerous species of domesticated animals with double muscled phenotypes, including sheep, chicken, mice, cattle, and pigs Kijas et al, 2007;Stinckens et al, 2008;Kim et al, 2022). Similar to our previous study (Lee et al, 2020), Mstn knock-out quail exhibited significantly heavier BW and greater breast muscle mass than WT quail, suggesting conserved function of Mstn in regulation of muscle growth between mammals and avian species.…”
Section: Discussionsupporting
confidence: 85%
“…However, to our knowledge, there are no studies that have reported both the muscle fiber type composition and meat quality characteristics in any poultry species. Although weights of chicken breast muscle having only type IIB myofibers were not significantly increased by Mstn mutation (Kim et al, 2022), weights of quail breast muscle containing both type IIA and IIB (Choi et al, 2014) were increased by Mstn mutation (Lee et al, 2020). Therefore, Mstn mutant quail can serve as a proper avian model to investigate effects of Mstn mutation on myofiber types and meat quality in poultry.…”
Section: Introductionmentioning
confidence: 96%
“…Sex differences are associated with growth performance in chickens [ 9 ], and genetic studies have reported that muscle characteristics, such as fiber CSA, have high heritability (>0.40) and exhibit significant positive genetic correlations with body and muscle weights in broilers between 4 and 6 weeks [ 13 ]. Moreover, muscle morphology is affected by many factors, such as breed [ 14 ], muscle type [ 10 ], age [ 11 , 13 , 15 ], and gene polymorphism [ 11 ]. In the present study, the muscle morphological characteristics of the breast and thigh muscles were assessed at different developmental stages, and the CSA of the breast and thigh muscles increased with age.…”
Section: Discussionmentioning
confidence: 99%
“…ImageJ software (NIH) was used to measure the muscle cell size. The average cross-sectional area (CSA) of myofiber was performed according to a previously published method [ 11 ]. Over 100 bundles of myofiber were measured for each animal.…”
Section: Methodsmentioning
confidence: 99%
“…As a result, the lower meat production has hindered the development of the goat industry. Postnatal muscle growth is positively correlated with muscle fiber diameter, with larger muscle fiber diameters resulting in faster muscle growth rates [ 1 , 2 ]. Recently, the studies of genome-wide transcription have provided a series of valuable candidate genes that regulate muscle growth in goats [ 3 , 4 ].…”
Section: Introductionmentioning
confidence: 99%